Cultura organizacional y compromiso afectivo en la unidad de gestión educativa local Loreto Nauta 2024 - Portillo Alarcon, Daniel (2025)
The main objective of the final report was to establish the relationship between organizational culture and affective commitment in the Loreto Nauta Local Educational Management Unit in 2024. The research was developed with a basic approach, at a descriptive-correlational level and non-experimental design. We worked with a population of 100 people, to whom a questionnaire was applied to collect information. The results indicated that the organizational culture in this entity is perceived as regular by 27% of the respondents. This is because, although sometimes the attitude and thinking of the staff influence the work team, only sometimes is it continuously trained, recognizing the organizational culture as a competitive advantage. In addition, the team almost always discusses their ideas and perspectives to reach consensus decisions. As for affective commitment, 32% rated it as regular, since only sometimes do employees feel a strong belonging to the institution and are willing to stay in it in the long term. Finally, it is concluded that there is a strong positive and statistically significant correlation between organizational culture and affective commitment in the Loreto Nauta LGU, with a correlation coefficient of 0.764 and a significance level of 0.000. These results confirm the existence of a direct relationship between both variables for the year 2024.